Can chronotype and social jet lag predict burnout among physical therapists?. Issue 10 (26th November 2021) - Mokros, Łukasz; Koprowicz, Jacek; Leszczyński, Piotr; Nowakowska-Domagała, Katarzyna; Witusik, Andrzej; Pietras, Tadeusz
ABSTRACT: Burnout syndrome can be described as a set of psychological and somatic responses to chronic stress related to professional work. The aim of this study was to verify whether chronotype and social jetlag (SJL) are predictors of burnout symptoms among physical therapists. The studied sample consisted of 61 physical therapists. Variables of interest included raw scores of the following tools: the Link Burnout Questionnaire (LBQ), Chronotype Questionnaire (CQ), Pittsburgh Sleep Quality Index (PSQI) and an authored questionnaire regarding sociodemographics and information required to calculate SJL. Linear regression models were constructed to predict LBQ dimension scores. An increase in the Psychophysical Exhaustion score was associated with a decrease in CQ Morningness-Eveningness (ME) score, an increase in CQ Distinctness of the Rhythm (DI) score and a decrease in SJL. Also, the Psychophysical Exhaustion score was higher for subjects reporting fairly poor quality sleep (PSQI) than for rating it as very good. An interaction was identified between SJL and ME. An increase in Sense of Professional Ineffectiveness was predicted by a decreased SJL score, and increased Disillusionment was associated with higher DI score. Both chronotype and SJL may prove useful predictors of certain aspects of burnout among physical therapists, but they should be considered together.